2016
DOI: 10.1111/cea.12844
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of inhaled corticosteroids and leukotriene modifiers: a systematic review

Abstract: There is a lack of replication of genetic variants associated with poor ICS or LTM response. The most consistent results were found for the FCER2 gene [encoding for a low-affinity IgE receptor (CD23)] and poor ICS response. Larger studies with well-phenotyped patients are needed to assess the clinical applicability of ICS and LTM pharmacogenomics/genetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 93 publications
(279 reference statements)
0
42
0
1
Order By: Relevance
“…A recent systematic review by Farzan et al [41] showed that genetic variants of three genes (GLCCI1, CRHR1, and FCER2) have been successfully replicated in at least one independent study.…”
Section: Ics Responsementioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review by Farzan et al [41] showed that genetic variants of three genes (GLCCI1, CRHR1, and FCER2) have been successfully replicated in at least one independent study.…”
Section: Ics Responsementioning
confidence: 99%
“…Initially, candidate-gene studies on LTRA response focused on genes within pharmacological leukotriene pathway, such as leukotriene A4 hydrolase (LTC4s), 5-lipoxygenase (ALOX5), leukotriene A4 hydrolase (LTA4H), and cysteinyl leukotriene receptor 1 (CysLTR1) [41]. In addition, genes influencing LTM pharmacokinetics such as CYP enzymes (CYP3A4, CYP2C9) and transporter genes (SLCO2B1, MRP1/ ABCC1) have also been investigated [53,54].…”
Section: Leukotriene Modifiers Responsementioning
confidence: 99%
See 1 more Smart Citation
“…According to the GINA guidelines, inhaled corticosteroids (ICS) combined with short‐acting β2 agonists (SABA), or long‐acting β2 agonists (LABA) are the preferred treatment for persistent asthma symptoms . However, even in asthmatic children with a good adherence to maintenance treatment and an adequate inhalation technique, there is a high variability in response to treatment; approximately ten percent of the patients still have serious complaints despite high doses of ICS …”
Section: Introductionmentioning
confidence: 99%
“…Pharmaco genomics is a subfield of genomics which assesses the effect of DNA variants on the patient's response to medication . Modulating effects of genetic variations, both focusing on asthma onset (genomics) as well as response to therapeutic agents (pharmacogenomics), have been reported in numerous studies . Single nucleotide polymorphisms (SNPs) are the most common type of genetic variation in the human genome and are commonly investigated in pharmacogenomics studies using candidate gene and genome wide association studies (GWAS).…”
Section: Introductionmentioning
confidence: 99%